Splenic B-cell marginal zone lymphoma with marked plasmocytic differentiation: tumor variant from Mott cells? - U. L. Julhakyan; V. N. Dvirnyk; L. P. Mendeleeva (Онкогематология, 2015)
Splenic B-cell marginal zone lymphoma (SMZL) – a rare B-cell non-Hodgkin, s lymphoma, which is represented morphologically by mature lymphoid cells, corresponding to lymphocytes of secondary follicles marginal zone by immunological characteristics. Plasma cell differentiation can be in marginal zone lymphoma, but we described a single case of abundance of Mott cells as a tumor substrate in splenic B-cell marginal zone lymphoma.We present the first case of SMZL represented by Mott cells. This was the second case of Mott cells tumor described in Russia.This observation is the only case among the collected material of splenic lymphomas. The morphological pattern is characterized by marked proliferation of monoclonal lymphoid cells with plasma cell differentiation with presence of Mott cells and is evidence of intense intracellular secretion of immunoglobulins.